CHARACTER EDUCATION IN THE 21ST CENTURY: A BIBLIOMETRIC ANALYSIS ON 2000-2024 SCOPUS DATABASE - Nurul Nadia Ibrahim; Noor Banu Mahadir Naidu; Punggothai Chandra Shegaram; Nur Suhaila Ahmad (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Character education has gained prominence in the 21st century as an essential aspect of developing well-rounded individuals equipped to navigate the moral and ethical complexities of modern society. This study conducts a bibliometric analysis of character education research published between 2000 and 2024, using the Scopus database to identify key trends, influential authors, leading institutions, and dominant themes in the field. The analysis reveals a growing body of literature that reflects the increasing significance of character education, particularly in regions such as Indonesia and the United States. The findings highlight the interdisciplinary nature of character education research, with significant contributions from social sciences, psychology, and the arts and humanities. This study provides a comprehensive overview of the evolution of character education, offering valuable insights for educators, policymakers, and researchers interested in the future direction of this critical area of study.